Measuring hydraulic properties of geotextiles after installation damage. Issue 5 (October 2017) - Cheah, C.; Gallage, C.; Dawes, L.; Kendall, P.
Abstract: Since geotextiles have been progressively incorporated into coastal protection structures, the influence of installation damage on them has been the primary concern. During installation/construction, geotextiles are repeatedly subjected to high mechanical stresses which often exceed service stress. It is therefore vital to evaluate the mechanical and hydraulic damage and determine the consequences of these damages to better develop criteria for selection of suitable products. As these damages could reduce the material's mechanical strength and hydraulic efficiency, or in the severest form of damage, puncturing, would end the separation function. The properties investigated in this paper include the permittivity and apparent opening size (AOS) of geotextiles. Generally, the greater the drop energy of armour units applied to geotextiles, the greater the potential for damage. Findings show that the residual permittivity could increase significantly, 45% during installation. The preliminary design of coastal structures will be optimised as engineers and designers can better estimate the amount of damage on geotextiles upon installation.